Global variations in prevalence of eczema symptoms in children from ISAAC Phase Three - Odhiambo, Joseph A; Williams, Hywel C; Clayton, Tadd O; Robertson, Colin F; Asher, M Innes; ISAAC Phase Three Study Group (N. Aıt-Khaled, H. R. Anderson, R. Beasley, B. Bjorksten, B. Brunekreef, J. Crane, P. Ellwood, C. Flohr, S. Foliaki, F. Forastiere, L. Garcı´a-Marcos, U. Keil, C. K. W. Lai, J. Mallol, E. A. Mitchell, S. Montefort, N. Pearce, A.W. Stewart, D. Strachan, E. von Mutius, S. K. Weiland, G.Weinmayr, G. Wong, P. Ellwood, E. A. Mitchell, A. Priftanji, B. Benhabyle`s, C. E. Baena-Cagnani, C. D. Crisci, M. Go´mez, G. E. Zabert, G. Haidinger, M. E. Howitt, J. Weyler, R. Pinto- Vargas, C. d. S. D. Bernhardt, W. G. Borges, P. A. M. Camargos, M. d. S. Cardoso, A. J. L. A. Cunha, G. B. Fischer, J. M. Motta, A. P. Neto, F. J. Passos, A. C. Pastorino, N. Rosario, A. Silva, D. Sole´, N.Wandalsen, M. de Britto, L. de Freitas Souza, T. Popov, C. Kuaban, A. Ferguson, D. Rennie, R. Goulding, P. Standring, P. Aguilar, L. Amarales, L. A. V. Benavides, M. A. Calvo, A. Contreras, Y.-Z. Chen, O. Kunii, Q. Li Pan, N.-S. Zhong, G. Aristiza´bal, ), A. M. Cepeda, G. A. Ordon˜ez, J. M’Boussa, R. Daniel, E. Soto-Quiro´s, B. N. Koffi, K. Lah Tomulic, P. Varona Pere´z, S. Barba, C. Bustos, M. L. Naguib, M. Figueroa Colorado, M.-A. Riikja¨rv, K. Melaku, R. Sa’aga-Banuve, J. Pekkanen, E. Vlaski, I. E. Hypolite, M. Gotua, U. Keil, J. Tsanakas, A. Bueso-Engelhardt, Y. L. Lau, G. Wong, Z. Novak, G. Zsigmond, S. Awasthi, S. Bhave, J. Chhatwal, N. M. Hanumante, K. C. Jain, M. K. Joshi, V. A. Khatav, L. Kumar, S. N. Mantri, A. V. Pherwani, S. Rego, M. Sabir, S. Salvi, G. Setty, S. K. Sharma, V. Singh, T. U. Sukumaran, P. S. Suresh Babu, C. B. Kartasasmita, P. Konthen, W. Suprihati, M.-R. Masjedi, A. Steriu, L. Armenio, L. Bisanti, E. Bonci, E. Chellini, G. Ciccone, V. Dell’Orco, C. Galassi, G. Giannella, S. La Grutta, M. G. Petronio, S. Piffer, P. Sestini, F. Abu-Ekteish, F. O. Esamai, L. Ng’ang’a, J. A. al-Momen, C. Imanalieva, S. Sulaimanov, V. Svabe, J. Bojarskas, J. Kudzyte, B. S. Quah, K. H. Teh, J. de Bruyne, M. Baeza-Bacab, M. Barraga´n-Meijueiro, B. E. Del-Rı´o-Navarro, R. Garcıa-Almaraz, S. N. Gonza´lez-Dı´az, F. J. Linares-Zapie´n, J. V. Merida-Palacio, N. Ramı´rez-Chanona, S. Romero-Tapia, I. Romieu, Z. Bouayad, R. Engels, R. MacKay, C. Moyes, P. Pattemore, Nicaragua: J. F. Sa´nchez, B. O. Onadeko, M. Magatogia, I. Annesi-Maesano, N. Mahmood, M. O. Yusuf, N. El Sharif, S. Mortaja, G. Cukier, J. A. Guggiari-Chase, P. Chiarella, F. Cua-Lim, A. Breborowicz, G. Lis, I. Annesi-Maesano, M. L. Chiera, R. Camara, J. M. Lopes dos Santos, C. Nunes, J. E. Rosado Pinto, L. Clancy, J.-M. Kayembe, I. Annesi-Maesano, D. Deleanu, E. G. Kondiourina, O. Y. Sow, P. Fuimaono, O. Adzovic, M. Hadnadjev, E. Panic, S. Zivanovic, Z. Zivkovic, D. Y. T. Goh, K. Voyi, H. J. Zar, H.-B. Lee, A. Arnedo-Pena, J. Batlles-Garrido, A. Blanco Quiro´s, R. M. Busquets, I. Carvajal-Uruen˜a, G. Garcia-Hernandez, C. Gonzalez Dıaz, F. Guille´n-Grima, A. Lo´pez-Silvarrey Varela, M. M. Morales Sua´rez-Varela, E. G. Pe´rez-Yarza, K. D. Gunasekera, O. A. A. Musa, O. Al-Rawas, H. Vogt, S. Mohammad, Y. Mohammad, K. Tabbah, J.-L. Huang, C.-C. Kao, A. Kongpanichkul, R. Nettagul, T. Prasarnphanich, J. Teeratakulpisarn, M. Trakultivakorn, P. Vichyanond, O. Tidjani, T. Iosefa, M. A. Monteil, M. Jerray, F. Khaldi, G. J. Redding, H. H.Windom, V. Ognev, H. R. Anderson, J. B. Austin, M. Burr, M. H. Shamssain, D. Holgado, M. C. Lapides, O. Aldrey, B. Vaen Cam, M. Sears, V. Aguirre, V. Ahel, C. Gratziou, C. K. W. Lai, J. Shah, K. Baratawidjaja, T. Fakakovi, R. Otten, S. Barny, R. Chansin, P. Manning, E. Bahati, R. M. Khaitov, N. Tuuau-Potai, B.-W. Lee, A. El Sony, L. Nilsson); E Vlaski (Elsevier BV, 2009)
Background: In 1999, The International Study of Asthma and Allergies in Childhood (ISAAC) Phase One reported the prevalence of eczema symptoms in 715,033 children from 154 centers in 56 countries by using standardized epidemiologic tools. Objective: To update the world map of eczema prevalence after 5 to 10 years (ISAAC Phase Three) and include additional data from over 100 new centers. Methods: Cross-sectional surveys using the ISAAC questionnaire on eczema symptoms were completed by adolescents 13 to 14 years old and by parents of children 6 to 7 years old. Current eczema was defined as an itchy flexural rash in the past 12 months and was considered severe eczema if associated with 1 or more nights per week of sleep disturbance. Results: For the age group 6 to 7 years, data on 385,853 participants from 143 centers in 60 countries showed that the prevalence of current eczema ranged from 0.9% in India to 22.5% in Ecuador, with new data showing high values in Asia and Latin America. For the age group 13 to 14 years, data on 663,256 participants from 230 centers in 96 countries showed prevalence values ranging from 0.2% in China to 24.6% in Columbia with the highest values in Africa and Latin America. Current eczema was lower for boys than girls (odds ratio, 0.94 and 0.72 at ages 6 to 7 years and 13 to 14 years, respectively). Conclusion:ISAAC Phase Three provides comprehensive global data on the prevalence of eczema symptoms that is essential for public health planning. New data reveal that eczema is a disease of developing as well as developed countries.
Keywords: eczema; prevalence; global; children; ISAAC; sex